Maternal Collapse during Caesarean Section: Two Case Reports - Pradhan, Ritu; Gurung, Tara; Shrestha, Sangeeta; Basnet, Ujjwol; Sharma, Kiran R; Shrestha, Amirbabu (Nepal Journal of Obstetrics and Gynaecology, 2016)
Obstetric haemorrhage is the leading cause of maternal collapse in our part of the world. That can result in cardiac arrest. Cardiac arrest during caesarean section is a rare complication which is challenging to both the anaesthesiologists and the obstetricians. Here we are reporting two case series of cardiac arrest during caesarean section following delivery of baby due to haemorrhage. Both the cases revived after prompt and active resuscitation followed by massive blood transfusion.